Synthesis, characterization, molecular docking, antimalarial, and antiproliferative activities of benzyloxy-4-oxopyridin benzoate derivatives - Marjan Mohebi; Neda Fayazi; Somayeh Esmaeili; Mahboubeh Rostami; Fereshteh Bagheri; Alireza Aliabadi; Parvin Asadi; Lotfollah Saghaie (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Malaria and cancer are two major health issues affecting millions of lives annually. Maltol complexes and derivatives have been extensively investigated as chemotherapeutic and antimalarial activities. In this study, the design, synthesis, biological activities, and docking study of a novel series of pyridinones derivatives were reported. Experimental approach: The chemical structures of synthesized compounds were approved by FTIR, 1HNMR, 13CNMR, and mass spectroscopies. The antimalarial activity was evaluated through β-hematin inhibition assay and the cytotoxicity activities were evaluated against PC12 and fibroblast cell lines via MTT and cell uptake assays. To theoretically investigate the ability of compounds to inhibit hemozoin formation, the synthesized compounds were docked in a heme sheet to explore their binding mode and possible interactions. Findings/Results: β-Hematin inhibition assay showed acceptable activity for 7f, 7c, and 7d compounds and the molecular docking study showed 7h and 7f had effective interactions with the heme sheet. The cytotoxic study revealed compound 4b (IC50 = 18 μM) was significantly more active against PC12 cells than docetaxel (IC50 = 280 μM). The observations of cell uptake images were also shown both cell penetration and monitoring potential of synthesized compounds. Conclusion and implications: The compounds showed a moderate ability to inhibition of heme polymerization and also good interaction with heme through molecular docking was observed. Additionally, some of them have a good cytotoxic effect on the study2 cell line. So further study on these compounds can lead to compounds that can be considered as anti-malarial and/or anticancer agents.